Glucose-lowering medications and glucose levels as the major determinants of progression of carotid atherosclerosis in middle-aged adults and elders: a community-based prospective study - Chou, Chao-Liang; Lu, Shu-Xin; Cheng, Chun-Fang; Wu, Tzu-Wei; Wang, Li-Yu (Frontiers in Endocrinology, 2024)
Background: Few prospective studies explored the incidence and determinant of carotid atherosclerosis (CA) progression (CAP). This community-based prospective study focused on the effects of diabetes mellitus (DM) treatments and glucose levels on CAP risks.We followed up a group of 657 CA-positive middle-aged adults and elders for CAP.CAP was defined as an increase in the total number of carotid plaque and/or an increase in diameter stenosis by at least 10%.Results: After 4.05 years of followed-up, CAP was detected in 364 (55.4%) subjects. The multivariable-adjusted hazard ratios (HRs) were 1.805 (95% confidence interval [CI]:1.374-2.358) and 0.694 (95% CI: 0.510-0.944) for elevated fasting plasma glucose (eFPG; FPG100 mg/dL) and glucose-lowering medications (GLM), respectively. As compared to GLM-negative+eFPG-positive subjects, the multivariable-adjusted HRs were 0.497 (95% CI: 0.373-0.662), 0.537(95% CI: 0.306-0.942), and 0.586 (95% CI: 0.412-0.833) for GLM-negative+eFPG-negative, GLM-positive+eFPG-negative, and GLM-positive+ eFPG-positive subjects, respectively. The multivariable-adjusted risks of CAP were similar between GLM-negative+eFPG-negative and GLM-positive+ eFPG-positive subjects (p=0.77).Stratified analyses showed that the multivariable-adjusted HRs per 5.0 mg/dL increase in FPG were significantly increased among GLM-negative subjects (HR=1.131; 95% CI: 1.094-1.171) and non-significantly decreased among GLM-positive subjects (HR=0.985; 95% CI: 0.957-1.013).We found that more than 50% of CA-positive subjects had CAP in 4 years and higher FPG significantly increased and GLM significantly decreased the risks of CAP.Additionally, GLM and FPG demonstrated an interactive effect on CAP risks. It seems possible that GLM may induces effects beyond lowering glucose levels and subsequently lowers CAP risks.